Greenland Peregrine Falcon eggshell thickness monitoring data 1972 - 2019 - Falk, Knud; Møller, Søren; Mattox, William G; Vorkamp, Katrin (Zenodo, 2020)
The Peregrine Falcon (Falco peregrinus tundrius) population in Greenland has been monitored in different survey areas in South and West Greenland since 1972. At visits to Peregrine Falcon nests, eggshell fragments from hatched eggs as well as addled (dead) eggs left behind have been collected with the aim of monitoring the thickness of the eggshells as well as analysing the whole eggs for contaminants. The shell thickness serves as a proxy for the falcons’ exposure to certain persistant organic pollutants, in particular DDT and its breakdown products (see summaries in Cade et al. 1988). This data set contains the raw data on 6665 eggshell thickness measurements of: 1. Whole eggs from South Greenland 1986-2015 2. Eggshell fragments from the study area in South Greenland 1981-2019 3. Eggshell fragments from the study area around Kangerlussuaq in West Greenland 1972-1989 The data set contains a mix of measurements of shell thickness including or excluding the eggshell membranes from the same clutch of eggs. Based on those measurements the average membrane thickness is 0.071 mm (SD=0.013) – a figure confirmed by other studies – and this ’membrane factor’ can be added or subtracted for comparisons with other data sets. Further details regarding the sampling areas, measurement methods and the results of trends analyses of changes in shell thickness are provided in Falk et al. (2006 and 2018). The file named 1_Data_Eggshell_Thickness_1972-2019.csv contains the raw measurements data and the file 2_ReadMe_Eggshell_Thickness_1972-2019.txt specifies the content. The file named 3_Rscript_Eggshell_Thickness_1972-2019.R provides an R script for summarizing and plotting the data as shown in the file 4_Plot_Eggshell_Thickness_1972-2019.pdf : Funded by the Danish Environmental Protection Agency as part of its Arctic Environmental Support Program. : {"references": ["Cade, T., Enderson, J., Thelander, C. & White, C. (eds.) 1988. Peregrine Falcon populations \u2013 their management and recovery. \u2013 The Peregrine Fund, Idaho", "Falk, K., M\u00f8ller, S., & Matox, W. G. (2006). A long-term increase in eggshell thickness of Greenlandic Peregrine Falcons Falco peregrinus tundrius. Science of the Total Environment, 355(1-3), 127. https://doi.org/10.1016/j.scitotenv.2005.02.024", "Falk, K., M\u00f8ller, S., Rig\u00e9t, F. F., S\u00f8rensen, P. B., & Vorkamp, K. (2019). Raptors are still affected by environmental pollutants: Greenlandic Peregrines will not have normal eggshell thickness until 2034. Ornis Hungarica, 26(2), 171-176. https://doi.org/10.1515/orhu-2018-0026"]}